Stratigraphic and paleogeographic distributions of Devonian crinoids from Spain with description of new taxa from the Iberian Chains. (November 2019) - Ausich, William I.; Zamora, Samuel
Abstract: A new Lower Devonian fauna from the Iberian Chains (NE Spain) is described. Specimens have been collected from the shaley intervals of the Mariposas Formation dated as early Emsian. These include the camerates Acanthocrinus carsli n. sp., Platyhexacrinus santacruzensis n. sp., Culicocrinus breimeri n. sp., Camerata indeterminate, and an indeterminate eucladid. Compared with other faunas from Spain, this represents a low diversity crinoid assemblage that was probably concentrated in shallow, turbid environments. A summary of crinoids previously described from the Spanish Devonian is reported, which indicates that crinoid faunas become progressively more cosmopolitan during the Devonian. UUID:http://zoobank.org:pub/2debf9fa-11bf-46df-baf1-ab7926031051